A study on the impact of stock options on firm performance. - Song, Sebastian Young Sun. (2008)
This paper examines the possible motivational effect of the Executive Stock Options Plan on corporate performance. This incentive scheme has been in existence since the 1990s and has rapidly gained popularity in the last decade. However, there has been equally varying results from past studies about its feasibility and viability and its superiority over other incentive schemes.